Myiodynastes chrysocephalus (Pschuvi, 1844), nueva especie para la Argentina - López Lanús, Bernabé M. (1992)
The first record of Myiodynasles chrysocephalus in Argentina is given, based on an individual seen and undoubtly identified in Mesón de Condado, Santa Victoria Departament, province of Salta. This is the southern most record species.